L-Theanine improves emulsification stability and antioxidant capacity of diacylglycerol by hydrophobic binding β-lactoglobulin as emulsion surface stabilizer. (1st January 2022) - Xue, Xiuheng; He, Haiyong; Liu, Cunjun; Wang, Li; Wang, Lu; Wang, Yueji; Wang, Luping; Yang, Chen; Wang, Juhua; Hou, Ruyan
Highlight: l -theanine conjugates β-lactoglobulin by hydrophobic interaction. Diacylglycerol emulsion stabilized by l -theanine and β-lactoglobulin complex was prepared. l -theanine and β-lactoglobulin complex was better to be used as stabilizers of diacylglycerol. l -theanine improves emulsification and antioxidant capacity of diacylglycerol emulsion. Abstract: Diacylglycerol (DAG) is commonly used as fat substitute in food manufacture due to its functional properties, but DAG has poor emulsification and oxidation stability, which limits its wide application in food industry. In this work, fluorescence quenching data and thermodynamic parameters were analyzed to investigate the interaction mechanism between l -theanine (L-Th) and β-lactoglobulin (β-LG). DAG emulsion was prepared by using β-lactoglobulin-theanine (β-LG-Th) as surface stabilizer, and its emulsification and oxidation stability were evaluated. The results showed that the hydrophobic interaction played an important role on the conjugate of β-LG and L-Th due to the negative values for ΔG, positive values for ΔH and ΔS at pH 4.0, pH 6.0 and pH 8.0. The DAG has been better embedded by using β-LG-Th as surface stabilizer, and the droplet size was about 0.2 µm to 1.5 µm when the pH was 6.0, the ratio of L-Th to β-LG was 1:1. β-LG-Th as surface stabilizer for DAG can increase the ζ-potential and emulsion index, make the emulsion droplet size distribution more uniform. The l -theanine was better to be used to improve the emulsification stability and antioxidant capacity of DAG by binding β-LG as surface stabilizer.